Effects of sodium benzoate on cognitive function in neuropsychiatric disorders: a systematic review and meta-analysis - Liang, Chun-Wei; Cheng, Hsiao-Yi; Tseng, Mei-Chih Meg (Frontiers in Psychiatry, 2024)
We performed a systematic review and meta-analysis on sodium benzoate’s effects on cognitive function and other psychiatric symptoms in individuals with neuropsychiatric disorders. We searched PubMed, Embase, Cochrane Library, and PsychInfo databases until September 2023. A random-effects meta-analysis was performed within a frequentist framework. To investigate the potential sources of heterogeneity, we performed subgroup analyses based on sex, dose, diagnosis, and risk of bias of the included studies. Trial sequential analyses were performed to investigate the statistical power of the synthesized studies. The certainty in evidence was evaluated using the Grading of Recommendations Assessment, Development and Evaluation approach. A total of 10 studies were included in the analysis. Sodium benzoate demonstrated a small-to-moderate positive effect on global cognitive function compared with placebo (standardized mean difference 0.40, 95% confidence interval 0.20 to 0.60, high certainty). Subgroup analyses suggested more pronounced effects in women; individuals receiving doses >500 mg/day; and individuals with early-phase Alzheimer’s disease, chronic schizophrenia, or major depressive disorder. Sodium benzoate also demonstrated potential efficacy in enhancing the speed of processing, working memory, verbal learning and memory, visual learning and memory, and reasoning and problem solving. Furthermore, sodium benzoate was effective for positive psychotic symptoms but not for negative psychotic and depressive symptoms with moderate certainty. The current evidence strongly supports the positive effects of sodium benzoate on cognitive function in neuropsychiatric disorders. Further research is required to confirm its efficacy across different subtypes or stages of neurocognitive disorders and within specific cognitive domains. Systematic Review Registration PROSPERO, identifier CRD42023457462